Konsep Demokrasi Dalam Reaslisme Politik - Mulyadi, Deddy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2006)
In general term, democracy involve people in government implementation reflected in phrase: â€œfrom the people, by the people, to the peopleâ€. There for, the government should develop the nation for the peopleâ€™s concern. The policy making and administrative practice are carried out by executive and legislative bodies which later deals with implementation and control system. In democracy, there are also several issues to consider namely political policy and administration, administrative accountability, subjective and objective accountability, type of spezsialized mobility and democratic mechanism. These issues will be briefly discussed in this articles.